1998
DOI: 10.1002/(sici)1097-0347(199812)20:8<745::aid-hed14>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase and its potential involvement in tumor invasion and metastasis

Abstract: Background Integrins are cell surface receptors which, in part, mediate the adhesion of cells to the extracelluar matrix. In addition to providing a molecular “glue” essential for tissue organization and survival, integrins are dynamic signaling molecules. Integrins allow normal, nontransformed cells to sense that they are adhered to the extracellular matrix, thus providing a cell survival signal. This signal allows cells to proliferate in the presence of growth factors and in some instances prevents apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(107 citation statements)
references
References 45 publications
3
103
0
Order By: Relevance
“…Additionally, aberrant trafficking of integrins to the leading edge has been documented to activate the matrix-degrading proteases such as matrix metalloproteinases (MMPs) and plasmin, required for degradation of the ECM and subsequent cell invasion [38,40]. Moreover, stimulation of cells with the growth factor heregulin (HRG), has been shown to affect the expression and serine phosphorylation status of the focal adhesion protein paxillin, resulting in both the induction of morphological changes in cell shape as well as the stimulation of cell scattering in the breast cancer epithelial cell line, MCF-7 [41][42][43]. Paxillin has also been implicated in contributing to tumor invasiveness and metastasis in breast cancer, non-small cell lung cancer, prostate cancer and osteosarcomas [41][42][43].…”
Section: Moving Toward Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, aberrant trafficking of integrins to the leading edge has been documented to activate the matrix-degrading proteases such as matrix metalloproteinases (MMPs) and plasmin, required for degradation of the ECM and subsequent cell invasion [38,40]. Moreover, stimulation of cells with the growth factor heregulin (HRG), has been shown to affect the expression and serine phosphorylation status of the focal adhesion protein paxillin, resulting in both the induction of morphological changes in cell shape as well as the stimulation of cell scattering in the breast cancer epithelial cell line, MCF-7 [41][42][43]. Paxillin has also been implicated in contributing to tumor invasiveness and metastasis in breast cancer, non-small cell lung cancer, prostate cancer and osteosarcomas [41][42][43].…”
Section: Moving Toward Metastasismentioning
confidence: 99%
“…Moreover, stimulation of cells with the growth factor heregulin (HRG), has been shown to affect the expression and serine phosphorylation status of the focal adhesion protein paxillin, resulting in both the induction of morphological changes in cell shape as well as the stimulation of cell scattering in the breast cancer epithelial cell line, MCF-7 [41][42][43]. Paxillin has also been implicated in contributing to tumor invasiveness and metastasis in breast cancer, non-small cell lung cancer, prostate cancer and osteosarcomas [41][42][43]. Lastly, over-expression of FAK has been documented in invasive and metastatic breast, colon, thyroid and prostate cancers [44,45].…”
Section: Moving Toward Metastasismentioning
confidence: 99%
“…In contrast, the (6 subunit is expressed in all carcinomas, (Kornberg, 1998;Almeida et al, 2000). FAK has been shown to be overexpressed in multiple invasive and metastatic tumor cancers (Komberg, 1998;Agochiya et al, 1999).…”
Section: L5j31mentioning
confidence: 99%
“…In our lab, human FAK was subsequently identified in high-grade sarcomas 12 and breast tumors. [13][14][15] FAK is overexpressed in a variety of human tumors in comparison with adjacent normal tissue, including breast, [13][14][15][16] colon, 13,14,17,18 thyroid, 19 ovarian, 20 cervix, 16 head and neck, 21 and esophagus. 22 Early work suggested that FAK might function in the later stages of tumor progression, such as invasion and metastasis, promoting adhesion in invading cells.…”
mentioning
confidence: 99%